Map memories: students in the ex-BIM 3 (Clío & Asociados. La historia enseñada. ISSN: 2362-3063, 2022)
This article is configured as a pedagogical proposal so that different high school students from the region know and visit the site of memory of the BIM 3. It is part of the university policies for the promotion of memory that the Facultad de Humanidades y Ciencias de la Educación and the Facultad de Psicología of the Universidad Nacional de La Plata, institutions that have been operating in this space since 2012 and 2014, respectively. Since then, different initiatives have been carried out to publicize the history of the place, among which the guides for entrants stand out, which are far from the current proposal, which is why it is constituted as a ‘pilot test’. We propose a group of tours for this place, which take place in some conferences, as well as different activities and materials, the road map is the most important learning tool. In this way, an original and innovative pedagogical device appears, so that the new generations can approach the history and memories of BIM 3 through their own experience as mapping makers of this site of memory, while reflecting, dialoguing, producing meanings that can be shared with others.
Keywords: students; memories; BIM 3